2007
DOI: 10.1002/cnm.1023
|View full text |Cite
|
Sign up to set email alerts
|

Tyings in linear systems of equations modelled with positive and negative penalty functions

Abstract: SUMMARYIn this short note, we focus on tyings (constraints that relate multiple degrees of freedom) modelled by means of penalty functions. In contrast to what is commonly thought, it is possible to obtain convergent results when negative penalty parameters are taken. A mathematical proof and an illustrating example are provided. In particular, we have proven that the results obtained with positive and negative penalty parameters enclose the exact solution from opposite sides. To this end, we have investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…As with traditional methods, the implementation is simple. The formulation of the constraint equation (2) and the equations of motion (6) describe the technique completely-except for the values of penalty parameters˛s and˛m, which are to be selected by the analyst. Because it is the magnitude of these parameters relative to the existing entries in K and M, which dictates the accuracy of the constraint imposition, penalty factors are often used to express the magnitude of the penalty, denoted by…”
Section: Bipenalty Matrix Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…As with traditional methods, the implementation is simple. The formulation of the constraint equation (2) and the equations of motion (6) describe the technique completely-except for the values of penalty parameters˛s and˛m, which are to be selected by the analyst. Because it is the magnitude of these parameters relative to the existing entries in K and M, which dictates the accuracy of the constraint imposition, penalty factors are often used to express the magnitude of the penalty, denoted by…”
Section: Bipenalty Matrix Formulationmentioning
confidence: 99%
“…Owing in part to their greater level of versatility, penalty methods have become a commonly chosen alternative. Examples include node‐to‐node tyings , interface elements/cohesive surfaces and contact conditions . Despite the fact that penalty methods only approximately impose the given constraints, they are often favoured over the Lagrange multiplier method because they are straightforward to implement, and they do not introduce any extra solution variables.…”
Section: Introductionmentioning
confidence: 99%
“…A long standing criticism of the penalty approach was the lack of a procedure to choose an appropriate magnitude for the penalty parameter, which must be large enough to effect a constraint but not too large as to cause numerical instability [1,2]. This has been addressed in some recent publications, which show how negative stiffness and positive and negative inertial type penalty parameters can be used to determine and control the error associated with any violation of the constraint(s) [8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Most of these papers provide the theoretical basis or simple applications for verification, but more recently negative penalty parameters have also been used in enforcing constraints in more complicated problems [3,22].…”
Section: Introductionmentioning
confidence: 99%
“…Ilanko and coworkers (Ilanko & Dickinson 1999;Ilanko 2002aIlanko ,b, 2003Ilanko , 2005aAskes & Ilanko 2006;Askes et al 2008) proposed the use of positive as well as negative values for the penalty parameters and they showed that the exact solution is bracketed by the results obtained with either positive or negative penalties. This result can be used to interpolate between results obtained with moderately large (but not very large) positive and negative penalty parameters.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years research has been carried out aimed at using lower values of the penalty parameters, while maintaining accuracy of constraint imposition, or aimed at penalty formulations that have a less adverse effect on the critical time step. Ilanko and coworkers (Ilanko & Dickinson 1999;Ilanko 2002aIlanko ,b, 2003Ilanko , 2005aAskes & Ilanko 2006;Askes et al 2008) proposed the use of positive as well as negative values for the penalty parameters and they showed that the exact solution is bracketed by the results obtained with either positive or negative penalties. This result can be used to interpolate between results obtained with moderately large (but not very large) positive and negative penalty parameters.…”
Section: Introductionmentioning
confidence: 99%